American studies, ecocriticism, and citizenship : thinking and acting in the local and global commons - Adamson, Joni, 1958-; Ruffin, Kimberly N., 1969- (Routledge interdisciplinary perspectives on literature, 2013)
This collection reclaims public intellectuals and scholars important to the foundational work in American Studies that contributed to emerging conceptions of an ""ecological citizenship"" advocating something other than nationalism or an ""exclusionary ethics of place."" Co-editors Adamson and Ruffin recover underrecognized field genealogies in American Studies (i.e. the work of early scholars whose scope was transnational and whose activism focused on race, class and gender) and ecocriticism (i.e. the work of movement leaders, activists and scholars concerned with environmental justice who